Towards a climate-resilient future together: A toolbox with participatory foresight methods, tools and examples from climate and food governance - Ende, Mandy van den; Wardekker, Arjan; Mees, Heleen; Hegger, Dries; Vervoort, Joost M. (Utrecht University, 2021)
The toolkit collects and showcases some of the lessons learned from several international research programs on citizen engagement in the form of practical exercises and advice on how to apply them.